FITRAH MANUSIA DALAM PERSPEKTIF PENDIDIKAN ISLAM - Tosan, Dimas Zonseta; Rahmah, Fina; Suryani, Sulistiyani; Bakar , M. Yunus Abu (Jurnal Muassis Pendidikan Dasar, 2023)
Human existence starts from a weakness and inability which will then move towards strength. Humans can easily take advantage of the grace and gifts bestowed on them, but humans must fulfill an obligation to their Lord. Human dignity in the sight of God is not measured by how high the rank, position, lineage or wealth. But what is measured by Allah is his piety. Humans in an Islamic perspective will still be born in a state of nature, namely holy, clean, free from all sins and have a tendency to accept religion, faith, and monotheism. Humans become good or bad is the result of educational and environmental factors, not their original character. Basically humans are born in a state of nature. This means that humans are born in an equally weak state even though they have great potential. But that doesn't mean that when a human is born, it's like a white or blank slate like John Lock said or helpless like a jabarian view. This is because humans have the potential in the form of certain tendencies related to their reasoning, mental, and psychic powers which are of different types and levels. The understanding of Islamic education experts on the nature of nature brings implications for the birth of the theory of nature in education. In the context of education, this theory becomes the basis for developing human nature. In this case, the educational process becomes important to improve its quality because it is one of the means that can develop the potentials that exist within humans in accordance with the nature of their creation which is in accordance with what is described in the Al-Qur'an and Hadith.